Method for improving high-temperature performance of TiAl alloy by using twin grid-containing gamma phase
By introducing the twin-containing grid gamma phase into the TiAl alloy, the problem of insufficient high-temperature tensile strength of polycrystalline TiAl alloy is solved, and higher high-temperature performance and operating temperature are achieved.
Patent Information
- Application Number
- CN202411762009.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-12-03
AI Technical Summary
The tensile strength of existing cast polycrystalline TiAl alloys at high temperatures of 900°C limits its application in high temperature environments.
By introducing a twin-containing grid gamma phase into the TiAl alloy, a specific element combination and smelting process is employed, including multiple smelting and rapid cooling in a vacuum non-consumable arc melting furnace to form a mesh twin gamma phase.
The high-temperature performance of TiAl alloy is significantly improved, including tensile strength and elongation at 900°C, reducing the formation of B2 phase, and improving the plasticity and high-temperature use temperature of the alloy.
Smart Images

Figure CN119553115A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for improving high temperature performance of TiAl alloy. Background Art
[0002] With the rapid development of aerospace, the high temperature service environment of aircraft engine blades has increased the requirements for material performance. As an important lightweight and high-strength structural material, TiAl alloy is considered to be an important candidate material for medium and low pressure turbine blades, and its microstructure and mechanical properties have received extensive attention.
[0003] TiAl alloy blades are usually made of polycrystalline TiAl alloy as raw materials for structural parts due to their large size and complex structure. However, the existing polycrystalline TiAl alloy has a high temperature tensile strength of 400-500 MPa at 900°C. In practical applications, its use is still limited, especially in higher temperature environments such as high-pressure combustion chambers of turbine blades. Therefore, it is necessary to develop a TiAl alloy with excellent high temperature performance at 900°C to promote the application of TiAl alloy in high temperature environments. Summary of the invention
[0004] The present invention aims to solve the problem of insufficient high temperature strength of existing cast polycrystalline TiAl alloys, and further provide a method for improving the high temperature performance of TiAl alloys by utilizing a twin-containing grid γ phase.
[0005] A method for improving the high temperature performance of TiAl alloy by using a twinned grid γ phase is carried out according to the following steps:
[0006] 1. Weigh the raw materials according to the atomic percentage of 35% to 60% Al, 2% to 7% Nb, 0.1% to 1% C, 0.8% to 3.2% Ta, 0.8% to 3.2% Hf and the balance Ti;
[0007] 2. Lay the raw materials in the water-cooled copper crucible mold of the vacuum non-consumable arc melting furnace from bottom to top in the order of melting points from high to low;
[0008] 3. Expel oxygen from the furnace and then introduce argon gas;
[0009] 4. Under an argon atmosphere, the input current is increased by 40A to 60A per minute until it reaches 900A to 1000A, and then smelting is carried out for 60s to 100s at a current of 900A to 1000A, and then the power is instantly cut off, and the molten alloy is cooled to room temperature using a water-cooled copper crucible to obtain an alloy ingot after primary smelting;
[0010] Fifth, the alloy ingot after the first smelting is repeatedly smelted according to step 4, thus completing the method of improving the high temperature performance of TiAl alloy by using the twinned grid γ phase.
[0011] The beneficial effects of the present invention are:
[0012] 1. The present invention will not cause the formation of a large amount of B2 phase through element design. Since the C element is an α-stabilizing element, the β-phase region is reduced, resulting in only a small amount of B2 phase in the alloy, and Ta coupled with Hf addition as a weak β-stabilizing element does not produce excess B2 phase. Due to its high hardness and brittleness, the B2 phase is prone to stress concentration during the stress process, thereby acting as a crack source to cause rapid failure of the alloy. Therefore, the present invention can effectively avoid the reduction of room temperature plasticity by reducing the B2 phase content. The TiAl alloy prepared by the present invention can achieve a compressive strength of 2300MPa to 2600MPa at room temperature, a compression rate of 38% to 42%, and good plasticity.
[0013] 2. The present invention obtains an intergranular γ phase containing network twins. Since the Hf element is a slow-diffusion element, the regions rich in Hf and β-stabilizing elements such as Al in the α phase are preferentially transformed into the γ phase during the solidification process. The migration of the α grain boundaries makes it possible for γ to be inside the α parent phase or at its boundary, and finally forms an intergranular γ phase. Due to the effect of Ta on reducing the stacking fault energy, the residual α phase around γ undergoes multiple twinning on the close-packed plane, and finally forms a γ phase with a twin grid. During the deformation process, the movement of dislocations to the twins is hindered, and the grid-like twins further confine the dislocations within the grid, which effectively stores and hinders the dislocations, thereby improving the high-temperature performance of the TiAl alloy. Thanks to the special element combination addition of the alloy composition and the rapid power failure during the smelting process, this unique structure, namely the intergranular γ phase containing network twins, is obtained.
[0014] 3. Generally, the ductile-brittle transition temperature of TiAl alloy is between 750℃ and 850℃. Above the ductile-brittle transition temperature, the strength of the alloy decreases rapidly. The TiAl alloy prepared by the present invention has a tensile strength of 550MPa to 650MPa at a high temperature of 900℃ and an elongation of 6% to 8%, which is higher than the polycrystalline TiAl alloy reported previously. The operating temperature of the TiAl alloy is increased by nearly 100℃, providing a theoretical composition reference for the preparation of high-performance TiAl alloy. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 Schematic diagram of the structure of the vacuum non-consumable arc furnace smelting system used in Example 1, 1 is a water-cooled copper crucible, 2 is a material turning device, 3 is a tungsten pole gun, 4 is a power control system, 5 is a circulating water cooling system, 6 is an argon protective gas introduction system, 7 is a vacuum control system, 8 is a mold, and 9 is a raw material;
[0016] Figure 2 The microstructure of the TiAl alloy prepared in Example 1 using a twinned grid γ phase to improve high temperature performance;
[0017] Figure 3 The microstructure of the TiAl alloy prepared in Example 2 using a twinned grid γ phase to improve high temperature performance;
[0018] Figure 4 This is a transmission microstructure diagram of a network twin reinforced γ phase formed in a TiAl alloy prepared in Example 2 that utilizes a twin network γ phase to improve high temperature performance;
[0019] Figure 5 Figure 1 is a room temperature compression performance diagram of the TiAl alloy prepared in Examples 1 and 2 using a twinned grid γ phase to improve room temperature performance, wherein 1 is Example 1 and 2 is Example 2;
[0020] Figure 6 The 900°C tensile performance diagram of the TiAl alloy prepared in Examples 1 and 2 using a twinned grid γ phase to improve high temperature performance, 1 is Example 1, and 2 is Example 2. DETAILED DESCRIPTION
[0021] Specific implementation method 1: This implementation method is a method for improving the high temperature performance of TiAl alloy by using a twin-containing grid γ phase, which is carried out in the following steps:
[0022] 1. Weigh the raw materials according to the atomic percentage of 35% to 60% Al, 2% to 7% Nb, 0.1% to 1% C, 0.8% to 3.2% Ta, 0.8% to 3.2% Hf and the balance Ti;
[0023] 2. Lay the raw materials in the water-cooled copper crucible mold of the vacuum non-consumable arc melting furnace from bottom to top in the order of melting points from high to low;
[0024] 3. Expel oxygen from the furnace and then introduce argon gas;
[0025] 4. Under an argon atmosphere, the input current is increased by 40A to 60A per minute until it reaches 900A to 1000A, and then smelting is carried out for 60s to 100s at a current of 900A to 1000A, and then the power is instantly cut off, and the molten alloy is cooled to room temperature using a water-cooled copper crucible to obtain an alloy ingot after primary smelting;
[0026] Fifth, the alloy ingot after the first smelting is repeatedly smelted according to step 4, thus completing the method of improving the high temperature performance of TiAl alloy by using the twinned grid γ phase.
[0027] In step 1 of this specific implementation method, there is a gradient in the melting points of the alloy components. During the smelting process, the low-melting-point Al and Ti melts can be used to better wrap the high-melting-point Ta and Hf elements, which is conducive to orderly heat transfer, thereby preparing an ingot with uniform composition.
[0028] In step three of this specific implementation method, by repeatedly removing oxygen from the furnace body, the oxygen content in the alloy ingot can be reduced, so that the performance of the alloy is excellent.
[0029] The fixed heating rate in step 4 of this specific implementation method ensures that the alloy smelting process is stable and controllable, and the alloy is cooled quickly by rapid power failure, and the diffusion of elements is limited, so that the intergranular γ phase is more easily formed.
[0030] In step five of this specific implementation method, repeated smelting is performed to avoid severe element segregation due to factors such as gravity, and the ingot structure and performance are more stable.
[0031] The beneficial effects of this embodiment are:
[0032] 1. This embodiment will not cause the formation of a large amount of B2 phase through element design. Since the C element is an α-stabilizing element, the β-phase region is reduced, resulting in only a small amount of B2 phase in the alloy, and Ta coupled with Hf addition as a weak β-stabilizing element does not produce excess B2 phase. Due to its high hardness and brittleness, the B2 phase is prone to stress concentration during the stress process, which acts as a crack source to cause rapid failure of the alloy. Therefore, reducing the B2 phase content in this embodiment can effectively avoid the reduction of room temperature plasticity. The TiAl alloy prepared in this embodiment can achieve a compressive strength of 2300MPa to 2600MPa at room temperature, and a compression rate of 38% to 42%, with good plasticity.
[0033] 2. This embodiment obtains an intergranular γ phase containing network twins. Since the Hf element is a slow-diffusing element, the regions rich in Hf and β-stabilizing elements such as Al in the α phase are preferentially transformed into the γ phase during the solidification process. The migration of the α grain boundaries makes it possible for γ to be inside the α parent phase or at its boundary, and finally forms an intergranular γ phase. Due to the effect of Ta on reducing the stacking fault energy, the residual α phase around γ undergoes multiple twinning on the close-packed plane, and finally forms a γ phase with a twin grid. During the deformation process, the movement of dislocations to the twins is hindered, and the grid-like twins further confine the dislocations within the grid, which effectively stores and hinders the dislocations, thereby improving the high temperature properties of the TiAl alloy. Thanks to the special element combination addition of the alloy composition and the rapid power failure during the smelting process, this unique structure, namely the intergranular γ phase containing network twins, is obtained.
[0034] 3. Generally, the ductile-brittle transition temperature of TiAl alloy is between 750℃ and 850℃. Above the ductile-brittle transition temperature, the strength of the alloy decreases rapidly. The TiAl alloy prepared in this embodiment has a tensile strength of 550MPa to 650MPa at a high temperature of 900℃ and an elongation of 6% to 8%, which is higher than the currently reported polycrystalline TiAl alloy. The operating temperature of the TiAl alloy is increased by nearly 100℃, providing a theoretical composition reference for the preparation of high-performance TiAl alloys.
[0035] Specific embodiment 2: This embodiment is different from specific embodiment 1 in that the raw materials described in step 1 are Al particles, AlNb master alloy blocks, C powder, Ta powder, Hf powder and Ti particles. The rest is the same as specific embodiment 1.
[0036] Specific implementation method three: This implementation method is different from specific implementation method one or two in that: the Al particles are regular quadrangular prisms with a base length of 2mm to 6mm and a height of 5mm to 9mm; the AlNb master alloy block is a regular quadrangular prism with a base length of 4mm to 7mm and a height of 6mm to 8mm; the particle size of the C powder is 100 mesh to 200 mesh; the particle size of the Ta powder is 300 mesh to 400 mesh; the particle size of the Hf powder is 200 mesh to 500 mesh; the Ti particles are cylinders with a diameter of φ2mm to φ4mm and a height of 3mm×5mm. Others are the same as specific implementation method one or two.
[0037] Specific embodiment 4: This embodiment is different from specific embodiments 1 to 3 in that in step 2, Ta powder, C powder, Hf powder, AlNb master alloy block, Ti particles, and Al particles are sequentially laid from bottom to top in a water-cooled copper crucible mold of a vacuum non-consumable arc melting furnace. Others are the same as specific embodiments 1 to 3.
[0038] Specific embodiment 5: This embodiment is different from specific embodiments 1 to 4 in that the removal of oxygen from the furnace body described in step 3 is specifically carried out according to the following steps: first, argon gas is introduced into the furnace body for 30s to 50s, and then vacuum is evacuated to a pressure of 10Pa to 20Pa, and the introduction of argon gas and vacuum are repeated 3 to 5 times. The rest is the same as specific embodiments 1 to 4.
[0039] Specific implementation method 6: This implementation method is different from specific implementation methods 1 to 5 in that in step 5, the alloy ingot after the first smelting is repeatedly smelted 5 to 10 times according to step 4. The rest is the same as specific implementation methods 1 to 5.
[0040] Specific embodiment 7: This embodiment differs from Specific embodiments 1 to 6 in that: before each repeated smelting in step 5, the alloy ingot is turned over by a turning device. The rest is the same as Specific embodiments 1 to 6.
[0041] Specific embodiment 8: This embodiment differs from Specific embodiments 1 to 7 in that: in step 1, raw materials are weighed according to atomic percentages of 47% Al, 6% Nb, 0.1% C, 1.6% Ta, 0.8% Hf and the balance Ti. The rest is the same as Specific embodiments 1 to 7.
[0042] Specific embodiment 9: This embodiment is different from specific embodiments 1 to 8 in that: in step 1, raw materials are weighed according to atomic percentages of 47% Al, 6% Nb, 0.1% C, 1.6% Ta, 1.6% Hf and the balance Ti. The rest is the same as specific embodiments 1 to 8.
[0043] Specific embodiment 10: This embodiment differs from specific embodiments 1 to 9 in that: in step 4, under an argon atmosphere, the input current is increased by 50A per minute until it reaches 1000A, and then smelting is performed for 60s under the condition of a current of 1000A, and then the power is instantly turned off, and the molten alloy is cooled to room temperature using a water-cooled copper crucible to obtain an alloy ingot after primary smelting. The rest is the same as specific embodiments 1 to 9.
[0044] The following examples are used to verify the beneficial effects of the present invention:
[0045] Embodiment 1:
[0046] A method for improving the high temperature performance of TiAl alloy by using a twinned grid γ phase is carried out according to the following steps:
[0047] 1. Weigh Al particles, AlNb master alloy block, C powder, Ta powder, Hf powder and Ti particles according to the atomic percentage of 47% Al, 6% Nb, 0.1% C, 1.6% Ta, 0.8% Hf and the balance Ti;
[0048] 2. Placing Ta powder, C powder, Hf powder, AlNb master alloy block, Ti particles, and Al particles in a water-cooled copper crucible mold of a vacuum non-consumable arc melting furnace in order from bottom to top according to the melting point from high to low;
[0049] 3. First, introduce argon gas into the furnace for 20 seconds, then evacuate to a pressure of 20Pa, repeat the introduction of argon gas and evacuation 4 times to remove oxygen from the furnace, and finally introduce argon gas;
[0050] Fourth, under an argon atmosphere, the input current is increased by 50A per minute until it reaches 1000A, and then smelting is performed at a current of 1000A for 60s, and then the power is instantly turned off, and the molten alloy is cooled to room temperature using a water-cooled copper crucible to obtain an alloy ingot after primary smelting;
[0051] 5. The alloy ingot after the first smelting is repeatedly smelted 6 times according to step 4, and before each repeated smelting, the alloy ingot is turned over by a turning device to obtain a TiAl alloy with improved high temperature performance by using a twinned grid γ phase.
[0052] The Al particles are regular quadrangular prisms of 3 mm (base length) × 7 mm (height); the AlNb intermediate alloy block is a regular quadrangular prism of 5 mm (base length) × 7 mm (height); the particle size of the C powder is 150 mesh; the particle size of the Ta powder is 300 mesh; the particle size of the Hf powder is 300 mesh; and the Ti particles are φ3 mm × 4 mm cylinders.
[0053] Embodiment 2: This embodiment is different from Embodiment 1 in that: in step 1, raw materials are weighed according to the atomic percentage of 47% Al, 6% Nb, 0.1% C, 1.6% Ta, 1.6% Hf and the balance Ti. The rest is the same as Embodiment 1.
[0054] Figure 1 The schematic diagram of the structure of the vacuum non-consumable arc furnace smelting system used in Example 1 is shown in Figure 1. 1 is a water-cooled copper crucible, 2 is a material turning device, 3 is a tungsten pole gun, 4 is a power control system, 5 is a circulating water cooling system, 6 is an argon protective gas introduction system, 7 is a vacuum control system, 8 is a mold, and 9 is a raw material. The raw material is placed in the mold of the water-cooled copper crucible, and the vacuum control system is used to evacuate the vacuum before smelting, and the arc furnace cavity is filled with argon as the protective gas. Then the power supply is provided by the power control system, and the tungsten pole gun is used as an electrode to break down and start the arc. The circulating water cooling system is always kept on during the smelting process. The material turning device is used to turn over the alloy ingot during multiple smelting. The water-cooled copper crucible is a water-cooled copper crucible, and there are 10 molds with a size of 80mm×100mm in the water-cooled copper crucible, so that the shape of the ingot is rectangular, and the single weight is 80g. The rectangular ingot is convenient for sample processing, the ingot utilization rate is high, and the single ingot weight of 80g can meet all tissue characterization and performance tests.
[0055] Figure 2 This is a microstructure diagram of the TiAl alloy prepared in Example 1 that uses twinned grid γ phase to improve high temperature performance; as can be seen from the figure, after adding 0.8Hf, the TiAl alloy presents a polycrystalline morphology composed of lamellar clusters, with γ phases between the lamellar clusters, and a small amount of B2 phase inside the lamellar clusters. Figure 3 This is a microstructure diagram of the TiAl alloy prepared in Example 2 that uses twinned grid γ phase to improve high temperature performance; it can be seen from the figure that after adding 1.6Hf to the TiAl alloy, there is a large amount of γ phase between grains and the distribution is relatively uniform. Figure 2 and Figure 3 It can be seen that with the increase of Hf element addition, the content of γ phase between grains increases, the content of B2 phase in the alloy further decreases, and the size of γ phase between grains also increases.
[0056] Figure 4This is a transmission microstructure diagram of the network twinning strengthened γ phase formed in the TiAl alloy prepared in Example 2 using the twinning network γ phase to improve the high temperature performance; it can be seen from the figure that a large number of network twins exist in the γ phase after adding 1.6Hf element. Hf element is a slow diffusion element, which stabilizes the β phase, so that the part enriched with Hf element is retained in the phase transformation as α phase and finally forms γ phase, and the residual α phase around it forms γ phase with network twins after multiple twinning.
[0057] Carry out room temperature compression performance test according to GB / T 7314-2017 test standard; Figure 5 The room temperature compression performance diagram of the TiAl alloy prepared in Examples 1 and 2 using a twinned grid γ phase to improve the room temperature performance, 1 is Example 1, and 2 is Example 2. It can be seen from the figure that the room temperature compressive strength of the alloy prepared in Example 1 is 2489MPa, and the compression rate is 38.8%; the room temperature compressive strength and compression rate of the alloy prepared in Example 2 are 2541MPa and 40.3%, respectively. This is because the B2 phase content in Example 2 is lower than that in Example 1, and the B2 phase, as a brittle phase, is prone to cracks during room temperature deformation, resulting in rapid fracture. The low B2 phase content increases the room temperature compression rate and improves the plasticity of the alloy. In addition, the network twins between grains can hinder dislocation movement, thereby increasing the strength of the alloy.
[0058] Conduct high temperature tensile performance test according to GB / T 228.2-2015 test standard; Figure 6 The 900°C tensile performance diagram of the TiAl alloy prepared in Examples 1 and 2 using a twinned grid γ phase to improve high temperature performance, 1 is Example 1, and 2 is Example 2. As can be seen from the figure, at 900°C, the tensile strength of the alloy prepared in Example 1 is 550MPa and the elongation is 6.5%; the tensile strength and elongation of the alloy prepared in Example 2 are 590MPa and 7.6%, respectively. This is because Example 2 contains more intergranular γ phase than Example 1, and the grid twin interface contained in the intergranular γ phase can serve as a barrier to hinder dislocation movement. At the same time, the formation of the grid confines the dislocations within the grid, avoiding dislocation pile-up and crack initiation at the phase interface. Thereby improving the high temperature strength and plasticity of the alloy.
Claims
1. A method for improving the high temperature performance of TiAl alloy by using a twinned grid γ phase, characterized in that It is carried out in the following steps:
1. Weigh the raw materials according to the atomic percentage of 35% to 60% Al, 2% to 7% Nb, 0.1% to 1% C, 0.8% to 3.2% Ta, 0.8% to 3.2% Hf and the balance Ti; 2. Lay the raw materials in the water-cooled copper crucible mold of the vacuum non-consumable arc melting furnace from bottom to top in the order of melting points from high to low; 3. Expel oxygen from the furnace and then introduce argon gas; 4. Under an argon atmosphere, the input current is increased by 40A to 60A per minute until it reaches 900A to 1000A, and then smelting is carried out for 60s to 100s at a current of 900A to 1000A, and then the power is instantly cut off, and the molten alloy is cooled to room temperature using a water-cooled copper crucible to obtain an alloy ingot after primary smelting; Fifth, the alloy ingot after the first smelting is repeatedly smelted according to step 4, thus completing the method of improving the high temperature performance of TiAl alloy by using the twinned grid γ phase.
2. The method of claim 1 for improving the high temperature performance of TiAl alloy by using a twinned grid γ phase, characterized in that The raw materials described in step 1 are Al particles, AlNb master alloy blocks, C powder, Ta powder, Hf powder and Ti particles.
3. The method of improving the high temperature performance of TiAl alloy by using a twinned grid γ phase according to claim 2, characterized in that The Al particles are regular quadrangular prisms with a base length of 2 mm to 6 mm and a height of 5 mm to 9 mm; the AlNb master alloy block is a regular quadrangular prism with a base length of 4 mm to 7 mm and a height of 6 mm to 8 mm; the particle size of the C powder is 100 mesh to 200 mesh; the particle size of the Ta powder is 300 mesh to 400 mesh; the particle size of the Hf powder is 200 mesh to 500 mesh; the Ti particles are cylinders with a diameter of φ2 mm to φ4 mm and a height of 3 mm×5 mm.
4. The method of improving the high temperature performance of TiAl alloy by using a twinned grid γ phase according to claim 2, characterized in that In step 2, Ta powder, C powder, Hf powder, AlNb master alloy block, Ti particles, and Al particles are laid in a water-cooled copper crucible mold of a vacuum non-consumable arc melting furnace from bottom to top.
5. The method of improving the high temperature performance of TiAl alloy by using a twinned grid γ phase according to claim 1, characterized in that The removal of oxygen from the furnace body described in step three is specifically carried out according to the following steps: first, argon gas is introduced into the furnace body for 30s to 50s, and then vacuum is evacuated to a pressure of 10Pa to 20Pa, and the introduction of argon gas and vacuum are repeated 3 to 5 times.
6. The method of claim 1 for improving the high temperature performance of TiAl alloy by using a twinned grid γ phase, characterized in that In step 5, the alloy ingot after the first smelting is smelted repeatedly 5 to 10 times according to step 4.
7. The method of claim 1 for improving the high temperature performance of TiAl alloy by using a twinned grid γ phase, characterized in that Before each repeated smelting in step 5, the alloy ingot is turned over by using a turning device.
8. The method of claim 1 for improving the high temperature performance of TiAl alloy by using a twinned grid γ phase, characterized in that In step 1, raw materials are weighed according to the atomic percentage of 47% Al, 6% Nb, 0.1% C, 1.6% Ta, 0.8% Hf and the balance Ti.
9. The method of claim 1 for improving the high temperature performance of TiAl alloy by using a twinned grid γ phase, characterized in that In step 1, raw materials are weighed according to the atomic percentage of 47% Al, 6% Nb, 0.1% C, 1.6% Ta, 1.6% Hf and the balance Ti.
10. The method of improving the high temperature performance of TiAl alloy by using twinned grid γ phase according to claim 1, characterized in that In step 4, under argon atmosphere, the input current is increased by 50A per minute until it reaches 1000A, and then smelting is carried out at a current of 1000A for 60s, followed by instantaneous power failure, and the molten alloy is cooled to room temperature using a water-cooled copper crucible to obtain an alloy ingot after primary smelting.
Citation Information
Patent Citations
TiAl alloy capable of separating out plenty of ordered omega phases and preparation method of TiAl alloy
CN114959361A
TiA1 based alloy, production process therefor, and rotor blade using same
EP1127949A2
Heat treatment method of castings from alloys based on gamma titanium aluminide
RU2502824C1